Multiple-Parallel Mediator Influence of Brand that connect with Consumer Attitude of Endorser to Purchasing Intention of Inkjet Business - Khiewritthirat, Narongchai; Narakorn, Prasittichai; Seesupan, Tummatinna; Udomthanavong, Surasit (Journal of Humanities and Social Sciences Thonburi University, 2024)
The purpose of this research was (1) to study Consumer Attitude of Endorser, Brand Credibility, Brand Attitude, Brand Trust, Brand Image and Purchased Intention. (2) to examine the influence of Consumer Attitude of Endorser, Brand Credibility, Brand Attitude, Brand Trust and Brand Image that affect Purchased Intention and (3) to analyze Multiple-Parallel Mediator Influence of Brand that connect with Consumer Attitude of Endorser to Purchasing Intention of Inkjet Business. Quantitative research was conducted using a survey method by questionnaire distributing 420 cases with a group of inkjet business, printing materials and advertisement in Thailand. Data were generated by mean, percentage and standard deviation. Test hypothesis by examining the structural equation model with smart PLS 4.0. The results showed that Consumer Attitude of Endorser significantly influences Brand Credibility, Brand Attitude, Brand Trust and Brand Image. Brand Credibility significantly influence Purchased Intention. Brand Attitude significantly influence Purchased Intention. Brand Image significantly influence Purchased Intention and Consumer Attitude of Endorser significantly influence Purchased Intention as well at the 0.01 level. However, Brand Trust failed to influence Purchased Intention.